Factors Influencing the Prospects of Zero Till Technology in Punjab (Indian Journal of Extension Education, 2019)
The zero-tillage technology is widely maintained as an integrated approach to conserve resources that can tackle the problem of wheat yield stagnation in the rice-wheat zone by improving planting time, reducing weed infestation, and enhancing fertilizer and water use efficiency. An attempt was made to assess the factors influencing the prospects of zero till technology in Punjab. A sample of 50 adopter farmers was selected by following cluster sampling design from Faridkot, Fazilka, Ferozepur, Gurdaspur, Hoshiarpur, Ludhiana, Mansa and Sangrur districts of Punjab state. The findings revealed that more than half (56.00%) of the farmers wanted to discontinue zero till drill in coming years. About one fourth (24.00%) of the farmers were willing to keep area constant under zero till drill. Majority of the farmers (68.00%) indicated to have favourable attitude towards zero till drill. Regarding functioning of zero till drill, it can only be used after straw removal (28.00%). Functioning of zero till drill also affected by stubbles (16.00%) as it needs fields to be cleaned properly. Determinants significantly influencing the prospects of zero till technology were age, operational land holding, family type, innovativeness, risk orientation and economic motivation of farmers.